2011
DOI: 10.1038/oby.2011.119
|View full text |Cite
|
Sign up to set email alerts
|

Altered Default Network Activity in Obesity

Abstract: The regulation of energy intake is a complex process involving the integration of homeostatic signals and both internal and external sensory inputs. To better understand the neurobiology of this process and how it may be dysfunctional in obesity, this study examined activity of the brain’s “default network” in reduced-obese (RO) as compared to lean individuals. The default network is a group of functionally connected brain regions thought to play an important role in internally directed cognitive activity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 48 publications
7
77
1
2
Order By: Relevance
“…Relevant to foodrelated behaviours, previous studies have found increased SN and DMN activity in obese individuals, both at rest and across task performance. [35][36][37] A small number of previous studies have investigated functional connectivity in people with anorexia nervosa, although, to our knowledge, ours is the first study to investigate the DMN and SN in currently ill women and to compare activity in these networks between ill and recovered women. Favaro and colleagues 38 found decreased activity in the ventral visual network in people with anorexia nervosa and those recovered from the disease compared with controls, but they also found increased activity in the somatosensory network in those with anorexia nervosa.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Relevant to foodrelated behaviours, previous studies have found increased SN and DMN activity in obese individuals, both at rest and across task performance. [35][36][37] A small number of previous studies have investigated functional connectivity in people with anorexia nervosa, although, to our knowledge, ours is the first study to investigate the DMN and SN in currently ill women and to compare activity in these networks between ill and recovered women. Favaro and colleagues 38 found decreased activity in the ventral visual network in people with anorexia nervosa and those recovered from the disease compared with controls, but they also found increased activity in the somatosensory network in those with anorexia nervosa.…”
Section: Introductionmentioning
confidence: 91%
“…As previous studies have found increased intrinsic DMN activity in obese individuals, we hypothesized that DMN activity in women with anorexia nervosa would be reduced and thus opposite to that seen in obesity. 35,37 Based on the findings of Cowdrey and colleagues, who showed increased DMN activity in individuals recovered from anorexia nervosa, we hypothesized that altered DMN activity is dependent on illness state and that reduced activity would be observed only in women with anorexia nervosa compared with controls. To our knowledge, no previous studies have investigated SN activity in women with anorexia nervosa or recovered women, but based on previous findings of increased SN activity in an obese sample, 36 we hypothesized that we would observe reduced SN activity in women with anorexia nervosa.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, overeating itself may give rise to ADHD-related symptoms. Some limited evidence suggests such an association; for example, short-term lab-based over-feeding studies in non-obese humans have been shown to lead to brain changes including an increase in the activation of the default mode network (DMN) [32]. ADHD is characterized by DMN over-activation and difficulty in suppressing this network during effortful tasks [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The brain plays a crucial role in the decision to eat by integrating the multiple hormonal and neuronal signals [3]. Not surprisingly, there is increasing evidence that obesity is associated with changes in the central nervous system [4][5][6][7][8].…”
Section: Q2mentioning
confidence: 99%